Belirli süreli iş sözleşmesi - Bozkurt Gümrükçüoğlu, Yeliz (My University, 2012)
Bir iş sözleşmesinin belirli veya belirsiz süreli olarak kurulması mümkündür. Belirli süreli iş sözleşmeleri sürenin sona ermesiyle birlikte kendiliğinden sona ermektedir. İş Kanununun 11. maddesine göre, İş ilişkisinin bir süreye bağlı olarak yapılmadığı halde sözleşme belirsiz süreli sayılır. Belirli süreli işlerde veya belli bir işin tamamlanması veya belirli bir olgunun ortaya çıkması gibi objektif koşullara bağlı olarak işveren ile işçi arasında yazılı şekilde yapılan iş sözleşmesi belirli süreli iş sözleşmesidir?. Böylece belirli süreli iş sözleşmelerinin geçerliliği objektif koşulun varlığına bağlanmıştır. Belirli süreli iş sözleşmesi ile çalıştırılan işçi, ayırımı haklı kılan bir neden olmadıkça, salt iş sözleşmesinin süreli olmasından dolayı belirsiz süreli iş sözleşmesiyle çalıştırılan emsal işçiye göre farklı işleme tâbi tutulamaz. Sürelendirme geçersiz olduğu takdirde sözleşme belirsiz süreli iş sözleşmesine dönüşecektir. Belirli süreli iş sözleşmeleri kural olarak sözleşmede kararlaştırılan sürenin dolmasından önce bir haklı nedenle derhal fesih hakkı olmadıkça feshedilemez.Bu çalışmada belirli süreli iş sözleşmesinin tanımı, geçerlilik koşulları ve sözleşmenin sona ermesi incelenmiştir.
Fixed-term contracts (employment agreement for definite period)
An employment agreement may be concluded for a definite or indefinite period of time. The agreement for a definite period of time terminates without any notice being required. According to the legal definition laid down in Art. 11 Labor Act ?An employment contract is deemed to have been made for an indefinite period where the employment relationship is not based on a fixed term. An employment contract for a definite period is one that is concluded between the employer and the employee in written form, which has a specified term or which is based on the emergence of objective conditions like the completion of a certain work or the materialisation of a certain event. Accordingly, the conclusion of a fixed-term contract is valid only if there is a objective conditions. An employee working under an employment contract for a definite period shall not be subjected to differential treatment in relation to a comparable employee working under an employment contract for an indefinite period. Accordingly, the fixed-term employment contract is regarded as being concluded for an indefinite period of time if the limitation is invalid. As a rule, a fixed term contract cannot be terminated before the end of the fixed term period, unless a right to break the contract for just cause.The dissertation examines the definition of fixed-term employment contract, the conditions of validity and expiry of a fixed term contract.
Keywords: Belirlilik; Definiteness; Geçici iş; Temporary work; İş sözleşmesi; Employment contract; İş ve Sosyal Güvenlik Mevzuatı; Employment and Social Secunity Law; İşçi-işveren ilişkileri; Employee-employer relations